1-methylnicotinamide attenuated inflammation and regulated flora in Necrotizing enterocolitis. - Lian Hou; Junbao Du; Jinxin Li; Qing Luo; Quan Kang (PLoS ONE)
Background Necrotizing enterocolitis(NEC) is a prevalent and destructive illness in neonates. Nicotinamide N-methyltransferase (NNMT) and its derivative, 1-methylnicotinamide (1-MNA), are known to be significant in conditions such as cardiovascular inflammation and renal tubular damage, and 1-MNA has been recognized for its anti-inflammatory effects in various diseases. However, the involvement of NNMT and 1-MNA in the development of NEC remains unclear. Methods We collected intestinal tissues and blood samples from children with NEC and control subjects for biochemical analysis. The NEC rats were induced by hypoxic cold stimulation and lipopolysaccharide, and control, NEC and NEC + 1-MNA groups were established. Neonatal rats were executed on the fourth day and blood, intestinal and fecal specimens were taken for subsequent testing. Results Elevated NNMT and 1-MNA were found in NEC children and NEC rats. Exogenous supplementation of 1-MNA to NEC rats reduced mortality, pathological and inflammatory damage, and inhibited activation of the TLR4-NF-κB pathway in neonatal rats. In addition, 1-MNA improved intestinal barrier function and modulated intestinal flora in NEC rats. Conclusion 1-MNA attenuated NEC injury by seemingly inhibiting the TLR4-NF-κB pathway, improving intestinal barrier function and modulating intestinal flora. These findings suggest a potential therapeutic role for 1-MNA in NEC management.